Vocational Teachers' Interest in Participating in Competency Certification Program from National Professional Certification Board - Yuni Anggraeni Muharam; Suryadi Suryadi; Sarkadi Sarkadi (STAI Hubbulwathan Duri, 2022)
This study aims to obtain the level of interest of vocational school teachers in the implementation of the competency certification program organized by the National Professional Certification Agency. Moreover, this competency certification is part of what is required in the era of globalization to produce quality graduates. This study uses a qualitative approach with a survey method. This research was conducted at a vocational school in Bekasi. Data was collected using interviews, documents, and questionnaires. The data analysis process uses the Miles and Huberman model through the process of data reduction, data presentation, drawing conclusions and triangulation. The results of the study concluded that there were 40% of schools encouraged teachers to take part in competency certification test training. Teachers need competency improvement activities such as training in mastery of competency certification test materials and also difficulties in keeping up with all developments in knowledge and technology. The table data shows that there are 60% of teachers interested in competency certification and desire to take the competency certification test.